Space, Region, and Power: Regional Boundary Conflicts in The Regional Autonomy Era - Mohammad Maiwan (SPATIAL: Wahana Komunikasi dan Informasi Geografi, 2019)
This study discusses the regional boundary conflicts that occurred in Indonesia during the era of regional autonomy. The conflict occurred because of a lack of planning, in the design of decentralization, as well as weak regulation. In reality, regional boundary conflicts hinder the implementation of government functions, reduce the level of service to the community, and potentially lead to legal uncertainty. Regional boundary conflicts, in the form of spatial conflicts (territories) are caused by several factors, namely: Economy, in the form of potential control of natural resources; political factors, related to electoral politics; juridical factors, weak legislation; social factors; historical and cultural factors; administrative technical factors, in the form of overlapping agency maps. As a way of solving it needs to be done through juridical settlement; regional cooperation bordering each other; and the application of one map policy. In addition, solutions can be through community participation, from various groups and social strata.